Cognitive impairment in patients with atrial fibrillation without stroke - Vineeth Jaison; Sarah Sharma; Himani Khatter; Rajneesh Calton; Jeyaraj Durai Pandian; Mahesh Pundlik Kate (Wolters Kluwer Medknow Publications, 2021)
Background: Vascular dementia is the second leading cause of dementia worldwide; however, the causation is multifactorial and may be preventable. There is increasing evidence that atrial fibrillation (AF) is independently correlated with cognitive decline. Assessing cognition in an outpatient setting is challenging. Gait speed may be able to transcend language in assessing cognition. We aim to assess cognitive impairment in patients with AF without known history of stroke with gait speed. Methods: This was a prospective, observational study of patients attending cardiology outpatient department. Patients were screened for a history of valvular or nonvalvular AF. Controls were patients without AF. Patients underwent structured interview, Montreal cognitive assessment (MoCA), and gait velocity assessment. Gait velocity and MoCA scores were compared in control and cases using Student's t-test. Results: A total of 189 patients were consented; 88 cases with AF and 101 controls. Mean ± standard deviation age was 60 ± 12 years. The median (interquartile range) gait velocity in patients with AF and nonAF was similar (0.80 [0.65-0.93] m/s vs. 0.80 [0.65-0.93] m/s, P = 0.708). The mean MoCA scores in patients with AF and without AF were also similar (17.38 ± 5.66 vs. 18.36 ± 5.30, P = 0.229). A cutoff value of <0.80 m/s had sensitivity of 66% and specificity of 61.4% to diagnose dementia. Conclusion: There is a high occurrence of cognitive deficits in patients with and without AF visiting a cardiology outpatient clinic. Future studies are needed to target this group of the patient to reduce the burden of vascular dementia.